PENINGKATAN KEMAMPUAN MOTORIK KASAR DAN KEPERCAYAAN DIRI MELALUI BERMAIN GERAK - AGUSRIANI, ADE (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: This study is aimed at exploring the gross motor skill and self confident processing activity of Group B students in TK Melati and investigating to what extend the processing result of gross motor skill and self confident can be improved through animal movement play. This study is a classroom action research using Kemmis and Mc. Taggart research model,and conducted in 2 cycles with 9 meetings in cycle 1 and 6 meetings in last cycle where every cycle consisted of the following steps: planning, action, observation and reflection. The sample of this study was 15 Group B students comprissing of 8 male students and 7 female students. The instruments used in this study was observational sheet of students activities using animal movement play. The data in this study were quantitative and qualitative data. Quantitative data were analyzed by using descriptive statistic to compare the result from the first and second cycle. While qualitative data from field notes and interview were analyzed through the following steps: data reduction, data display and data verification. The results of this study depicts that there was the improvement of gross motor skilland self confident through animal move play, proven by the gross motor skill mean score in pre-cycle which was 64,17 % had improvement to 77,35 % in cycle I and become 89,13 % in cycle II. Keywords: move play, gross motor skill, self confident, early childhood